Waves in contract and liability law in three decades of Ius commune / editors: Anne Keirse, Marco Loos. - Keirse, Anne L.M; Loos, Marco, 1969- (Ius commune europaeum ;, 2017)
This book revolves around major legal developments in the fields of European contract law and tort law from 1981 to today and examines whether similarities or divergences can be observed. It examines how opposing concepts such as weaker party protection (consumers as well as SME) and freedom of contract and fault principle are balanced. It also focuses on Europeanisation and constitutionalisation of both contract and tort law and the need to adjust the law in response to digitalisation and new technological, environmental or financial risks. Furthermore, the law of obligations nowadays emerges from very different sources and directions (top-down, bottom-up, but also crossing-over and diagonal). Norms of the law of obligations are not only being made by national legislators and courts, but also by European institutionalised lawmakers and (increasingly important) by private actors, organisations and networks. This book illustrates that the law of obligations evolves in a continuing process of waves. Contradictory tendencies in contract law alternate in focuses on the demands of the free market and the core value of party autonomy on the one hand and on the concept of fairness and weaker-party protection on the other hand. Tort law shows movements discarding former limitations of liability and embracing liability of wider scope and vice versa returns to more restricted approaches.